FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA MANAJERIAL DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERATING - Nissa, Fachrun; Astuti, Widia; Sari, Eka Nurmala (KRISNA: Kumpulan Riset Akuntansi, 2022)
The purpose of this study is to determine and analyze whether budget participation has an effect on managerial performance. To find out and analyze whether the clarity of budget targets has an effect on managerial performance. To find out and analyze whether organizational culture moderates the effect of budget participation on managerial performance. To find out and analyze whether organizational culture moderates the effect of budget target clarity on managerial performance.The research approach uses quantitative associative. This research uses data analysis method using SmartPLS.3 software which is run with computer media. In this study, the research instrument used was a questionnaire/questionnaire. The variable measurement scale used in this study is to use an ordinal scale in the form of a Likert scale. The sample of this study is the entire population of 35 employees at PT. KIM. Based on the results of the research, budget participation has a significant positive effect on managerial performance. Budget target class has a significant positive effect on managerial performance. Organizational culture can moderate the effect of budgetary participation on managerial performance. Organizational culture can moderate the influence of the budget target class on managerial performance